PENGARUH PENGALAMAN BELANJA ONLINE TERHADAP NIAT BELI ULANG DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI (Survei pada Konsumen Batik Pangastuti di Beteng Trade Center Solo) - Novi Dwi Ariyani; Marjam Desma Rahadhini; Sumaryanto Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2021)
The purpose of this study was to analyze the significance of online shopping experience on repurchase intentions through trust in consumers of Batik Pangastuti at Beteng Trade Center Solo. The population of this research is consumers of Batik Pangastuti who have made batik fashion product purchases online at least 2 times using probability sampling methods with a sample of 85 respondents. Data collection techniques using a questionnaire. Methods of data analysis using the sobel test. The results of this study indicate that the experience of online shopping has a positive and significant effect on repurchase intentions. Trust has a positive and significant effect on repurchase intentions. Trust is able to significantly mediate the effect of online shopping experience on repurchase intentions.